Optimisation of sample preparation and analysis conditions for atom probe tomography characterisation of low concentration surface species. (21st July 2016) - Douglas, J O; Bagot, P A J; Johnson, B C; Jamieson, D N; Moody, M P
Abstract: The practicalities for atom probe tomography (APT) analysis of near-surface chemistry, particularly the distribution of low concentration elements, are presented in detail. Specifically, the challenges of surface analysis using APT are described through the characterisation of near-surface implantation profiles of low concentration phosphorus into single crystal silicon. This material system was chosen to illustrate this surface specific approach as low concentration phosphorus has significant mass spectra overlaps with silicon species and the near surface location requires particular attention to focused ion beam specimen preparation and deposition of various capping layers. Required changes to standard sample preparation procedure are described and the effects of changes in APT analysis parameters are discussed with regards to this specific material system. Implantation profiles of 14 kV phosphorus ions with a predicted peak concentration of 0.2 at .% were successfully analysed using APT using pulsed laser assisted evaporation. It is demonstrated that the most important factor in obtaining the most accurate implantation profile was to ensure all phosphorus mass peaks were as free of background noise as possible, with thermal tails from the Si 2+ ions obscuring the P 2+ ions being the major overlap in the mass spectrum. The false positive contribution to the phosphorus profiles from hydride species appears minimal at the capping layer/substrate interface. The initial capping layer selection of nickel was successful in allowing the analysis of the majority of the phosphorus profile but nickel and phosphorus mass spectra overlaps prevent optimum quantification of phosphorus at the surface.